Analysis of the Accounting Information System for Umrah and Hajj Ticket Sales at PT. Tawwaabiin Umroh Haji Plus Sedayulawas: ANALISIS SISTEM INFORMASI AKUNTANSI PENJUALAN TIKET UMROH DAN HAJI DI PT. TAWWAABIIN UMROH HAJI PLUS SEDAYULAWAS - Adji Roy Widiyantoro; Anik Puji Handayani (Journal Financial, Business and Economics, 2025)
Tawwaabiin Umroh and Hajj Plus is a company engaged in organizing Umrah and Hajj pilgrimage tours. The implementation of a Sales Accounting Information System (SIA Penjualan) in Umrah and Hajj pilgrimage service companies plays a significant and crucial role in supporting the smooth operation of the company, as well as promoting accountable and effective financial management. This research aims to analyze the implementation of the Umrah and Hajj ticket sales accounting information system and provide solutions for findings related to this Sales Accounting Information System. The method used is descriptive qualitative, drawing on data from interviews, observations, and documentation, or triangulation. This study indicates that the analysis of the Umrah and Hajj ticket sales Accounting Information System at PT. Tawwaabiin is adequate, but some improvements are needed, such as the absence of segregation of related functions within the Umrah and Hajj ticket sales accounting information system, or the lack of a clear separation of organizational structure in conducting company activities.